Agriculture related corneal injuries - Goel, Ruchl; Malik, KPS; Goel, A; Sharma, N; Aggarwal, A (Nepalese Journal of Ophthalmology, 2013)
Introduction: Agricultural workers are predisposed to corneal injuries, which, if neglected, can lead to corneal blindness. Objective: To study the prevalence and mode of agriculturerelated corneal injuries in the village of Badkali, MuzaffarNagar, Western Uttar Pradesh, India in 2005 – 2006. Subjects and methods: Adult population of village Badkali, MuzaffarNagar, Uttar Pradesh. A door-to-door survey was carried out by paramedical ophthalmic assistants in October and November 2007. The main outcome measure was occurrence of corneal trauma in the fields from January 2005 until December 2006, its mode of injury, symptoms, treatment taken and outcome. Results: The study area comprised of 718 people, of whom 584 were engaged in agricultural activities and 481 were male. While working on the fields, 221 persons sustained corneal injuries and out of them four were injured more than once. The number of injuries caused due to sugarcane leaves, wheat , cattle tail/ ear, ‘cheri leaves’ and others were 83(36.7 %), 24(10.6 %), 60(25.5 %), 31(13.7 % )and 28(12.4 %) respectively. All were closed globe injuries except for two. Out of the 221 injured, 117 (51.7 %) took treatment and 95(42.2 %) had a best corrected visual acuity < 6/18. Conclusion: The majority of the population in Badkali were employed in farming. Logistic regression shows that the occurrence of injuries was more in those engaged in farming and related activities as compared to other occupations (OR = 0.012, p = 0.000, 95 % CI = 0.02, 0.09) and the maximum number of injuries being caused by sugar cane leaves followed by cattle tails. Nepal J Ophthalmol 2013; 5(9):45-49 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7821